# How do you simplify #x^2*x^sqrt3#?

##### 1 Answer

Jan 29, 2017

#### Answer:

#### Explanation:

Imagine, first, we wanted to simplify the expression

Then,

#x^2*x^3=overbrace(x*x)^(x^2)*overbrace(x*x*x)^(x^3)=overbrace(x*x*x*x*x)^(x^5)=x^5#

In general, we can write that:

#x^a*x^b=overbrace(x*x*...*x)^("x multiplied a times")*overbrace(x*x*...*x)^("x multiplied b times")=overbrace(x*x*...*x)^("x multiplied a+b times")=x^(a+b)#

In the given problem, one of the powers is

#x^2*x^sqrt3=x^(2+sqrt3)#